2015
DOI: 10.1016/bs.agron.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Host Plant and Rhizobium Genomics to Enhance Symbiotic Nitrogen Fixation in Grain Legumes

Abstract: This chapter was originally published in the book Advances in Agronomy. The copy attached is provided by Elsevier for the author's benefit and for the benefit of the author's institution, for non-commercial research, and educational use. This includes without limitation use in instruction at your institution, distribution to specific colleagues, and providing a copy to your institution's administrator. All other uses, reproduction and distribution, including without limitation commercial reprints, selling or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 445 publications
1
84
0
4
Order By: Relevance
“…In the USA, for example, heavy applications of N fertilizer may have limited nitrogen fixation capacity of soybean (Chang et al, 2015). As yield potential is a result of several genes, neglecting N 2 -fixation-related genes may result in cultivars that are less responsive to rhizobial inoculation, and more dependent on N fertilizers (Graham and Vance, 2000;Dwivedi et al, 2015). Indeed, Kiers et al (2007), by performing experiments with old and new soybean cultivars, have found that soybean breeding in the USA has contributed to loosen efficient rhizobial symbioses in the field.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the USA, for example, heavy applications of N fertilizer may have limited nitrogen fixation capacity of soybean (Chang et al, 2015). As yield potential is a result of several genes, neglecting N 2 -fixation-related genes may result in cultivars that are less responsive to rhizobial inoculation, and more dependent on N fertilizers (Graham and Vance, 2000;Dwivedi et al, 2015). Indeed, Kiers et al (2007), by performing experiments with old and new soybean cultivars, have found that soybean breeding in the USA has contributed to loosen efficient rhizobial symbioses in the field.…”
Section: Discussionmentioning
confidence: 99%
“…van Kessel and Hartley (2000), when analyzing sets of experiments before and after increased use of N fertilizer in soybean reached similar conclusion. In Africa, where suitable rhizobial inoculants are scarce for socio-economic reasons, soybean breeding has promoted the release of promiscuous soybean cultivars, meaning that they are less responsive to inoculation with soybean elite specific strains, but able to nodulate with indigenous bradyrhizobia (Graham and Vance, 2000;Dwivedi et al, 2015). In the places mentioned above and perhaps in other places (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations